1998
DOI: 10.1073/pnas.95.18.10996
|View full text |Cite
|
Sign up to set email alerts
|

Transport of uncharged organic solutes in Xenopus oocytes expressing red cell anion exchangers (AE1s)

Abstract: When expressed in Xenopus oocytes, the trout red cell anion exchanger tAE1, but not the mouse exchanger mAE1, elicited a transport of electroneutral solutes (sorbitol, urea) in addition to the expected anion exchange activity. Chimeras constructed from mAE1 and tAE1 allowed us to identify the tAE1 domains involved in the induction of these transports. Expression of tAE1 (but not mAE1) is known to generate an anion conductance associated with a taurine transport. The present data provide evidence that (i) the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 17 publications
0
18
1
Order By: Relevance
“…Effect of 10 Ϫ6 M bumetanide and Cl Ϫ or Na ϩ removal was also measured on Rb influx in tAE1-expressing oocyte. The Rb influx in Cl Ϫ -free medium was done in isosmotic NO 3 Ϫ -containing MBS, as published previously (14). The Na ϩ -free medium was MBS in which N-methyl-D-glucamine was substituted for Na ϩ (see "Experimental Procedures" for media composition).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Effect of 10 Ϫ6 M bumetanide and Cl Ϫ or Na ϩ removal was also measured on Rb influx in tAE1-expressing oocyte. The Rb influx in Cl Ϫ -free medium was done in isosmotic NO 3 Ϫ -containing MBS, as published previously (14). The Na ϩ -free medium was MBS in which N-methyl-D-glucamine was substituted for Na ϩ (see "Experimental Procedures" for media composition).…”
Section: Resultsmentioning
confidence: 99%
“…All of the AE polypeptides can be divided into two main domains of about the same size: an N-terminal cytoplasmic domain interacting with cytoskeleton and a membrane spanning domain, which is responsible for ion translocation, with a short C-terminal end in the cytoplasm. By expression studies of tAE1 in Xenopus oocytes, we have demonstrated previously that this normally electroneutral anion exchanger is able to form an anion conductive path-way permeable to different charged or neutral osmolytes such as urea, choline, sorbitol, Na ϩ , and K ϩ (13)(14)(15). In physiological conditions, these transport properties of tAE1 are activated by a decrease in intracellular ionic strength in swollen erythrocytes, and they are involved in the cell regulatory volume decrease response (16,17).…”
mentioning
confidence: 99%
“…In erythrocytes of a number of species, the volume-stimulated taurine efflux appears to occur by a transport pathway that involves band 3 (2,3). Oocyte expression of band 3 cloned from trout, but not mouse, results not only in a Cl Ϫ exchange activity, but also in a swelling-activated pathway for a number of solutes including taurine (4). This latter finding strongly supports a role for band 3 as either the volumeactivated transporter or a component of a volume-activated taurine transport pathway.…”
mentioning
confidence: 99%
“…Inclusion of the cytoplasmic domain of band 3 in this assay showed that only Syk and Lyn can directly phosphorylate the cytoplasmic domain of band 3. Upon cell volume expansion, Syk activity was increased as assessed by three different assays (immune complex assay measuring autophosphorylation, assay of the level of phosphotyrosine of the immunoprecipitated kinase, and assay of level of 32 P in the kinase immunoprecipitated from cells prelabeled with 32 PO 4 and then volume-expanded). The tyrosine kinase Lyn was also stimulated by volume expansion, most notably when analyzed by the latter two methods.…”
mentioning
confidence: 99%
“…In fact, tAE1 will also allow significant transport of organic osmolytes (e.g. taurine) and even significant Na and K fluxes (Fievet et al 1995(Fievet et al , 1998. Physiologically this multifunctional property of tAE1 plays a role in cell volume regulation in response to swelling (Guizouarn et al 2001).…”
Section: Introductionmentioning
confidence: 99%